2016
DOI: 10.5539/ijef.v8n2p171
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Performance of the Fractal Adaptive Moving Average Strategy: The Case of EUR/USD

Abstract: Most technical analysis tools focus traditionally on the simple and exponential moving average technique. This study looks at the performance of an optimized fractal adaptive moving average strategy over different frequency intervals, where the Euro/US Dollar currency pair is analyzed due to the increased correlation between the Euro Index and EUR/USD, and the Dollar Index and EUR/USD over the last year compared to the last 15 years. The optimized strategy is evaluated against a buy-and-hold strategy over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…SLB reported the smallest Sharpe value of 0.30, compared to PSX which shared the highest excess return per unit of total risk. In line with Gurrib and Elshareif (2016), who proposed to adjust the Sharpe ratio to the number of trades as a proxy to transaction costs, PSX reported the highest Sharpe per number of trade value of 0.0118, compared to XOM which had the lowest Sharpe value per number of trades, due to the relatively high number of trades. To assess the impact of only downside risk over the performance of each stock, the Sortino values were also calculated and reported.…”
Section: Performance Evaluationmentioning
confidence: 70%
“…SLB reported the smallest Sharpe value of 0.30, compared to PSX which shared the highest excess return per unit of total risk. In line with Gurrib and Elshareif (2016), who proposed to adjust the Sharpe ratio to the number of trades as a proxy to transaction costs, PSX reported the highest Sharpe per number of trade value of 0.0118, compared to XOM which had the lowest Sharpe value per number of trades, due to the relatively high number of trades. To assess the impact of only downside risk over the performance of each stock, the Sortino values were also calculated and reported.…”
Section: Performance Evaluationmentioning
confidence: 70%
“…Some authors in existing literature provide a good review of pioneer trend-following systems such as the Dow Theory, upon which today's Dow Jones Industrial Average is based [34,35]. More recent advancements in the field of average-based techniques include an adaptive moving average model for the Euro/US dollar currency pair and achieved higher annualized returns, lower annualized risk, but accompanied with higher number of trades, than the naïve buy-and-hold strategy [36]. An optimized moving average crossover strategy over the SPDR S&P 500 ETF suggested that the trend-following strategy outperform a buy-and-hold strategy [37].…”
Section: Technical Analysis Based Strategiesmentioning
confidence: 99%
“…Recent advancements in the field of average based techniques include Gurrib and Elshareif (2016) who tested an adaptive moving average model for the Euro/US dollar currency pair and achieved higher annualized returns, lower annualized risk, but accompanied with higher number of trades, than the naïve buyand-hold strategy. Gurrib (2016) applied an optimized moving average crossover strategy over the SPDR S and P500 ETF and found that the trend following strategy outperform a buy-and-hold strategy.…”
Section: Measuring Technical Analysis Performancementioning
confidence: 99%